Long-term outcomes of the current remote magnetic catheter navigation technique for ablation of atrial fibrillation. (2nd November 2017) - Yuan, Shiwen; Holmqvist, Fredrik; Kongstad, Ole; Jensen, Steen M.; Wang, Lingwei; Ljungström, Erik; Hertervig, Eva; Borgquist, Rasmus
Abstract: Objectives. Comparisons between remote magnetic (RMN) and manual catheter navigation for atrial fibrillation (AF) ablation have earlier been reported with controversial results. However, these reports were based on earlier generations of the RMN system. Design. To evaluate the outcomes of the most current RMN system for AF ablation in a larger patient population with longer follow-up time, 112 patients with AF (78 paroxysmal, 34 persistent) who underwent AF ablation utilizing RMN (RMN group) were compared to 102 AF ablation patients (72 paroxysmal, 30 persistent) utilizing manual technique (Manual group). Results. The RMN group was associated with significantly shorter fluoroscopy time (10.4 ± 6.4 vs. 16.3 ± 10.9 min, p < .001) but used more RF energy (64.1 ± 19.4KJ vs. 54.3 ± 24.1 KJ, p < .05), while total procedure time showed no significant difference (201 ± 35 vs. 196 ± 44 min, NS). After 39 ± 9/44 ± 10 months of follow-up, AF-free rates at 1year, 2 years and 3.5 years post ablation were 63%, 46% and 42% in the RMN group vs. 60%, 32% and 30% (survival analysis p < .05) in the Manual group, whereas clinically effective rates were 82%, 73% and 70% for the former vs. 70%, 56% and 49% for the latter (survival analysis p < .005). Conclusion. Differing from previous reports, our data from a larger patient population and longer follow-up time demonstrates that compared to manual technique, the most current RMN technique is associated with better procedural and clinical outcomes for AF ablation.